(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
This review examines the photocatalytic degradation of organic pollutants using nano-semiconductor photocatalysts, particularly those derived from onion peel extract, as a sustainable solution for wastewater treatment. It highlights the high catalytic activity, cost-effectiveness, and solar energy utilization of these materials. Recent advancements in magnetic nano-semiconductors offer improved separation and reusability, addressing key limitations. Modified photocatalysts such as TiO₂ and ZnO it synthesized via sol-gel, microwave, and ultrasonication, methods, show strong potential for greywater treatment. The integration of photocatalysis with oxidants like Fe³⁺ enhances mineralization efficiency. Operational parameters including pH, pollutant concentration, and catalyst loading are also discussed for process optimization. This review identifies promising directions for scalable and efficient photocatalytic wastewater treatment.